1997
DOI: 10.2166/wst.1997.0068
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of biofilm growth and water quality changes in sewers with anoxic and anaerobic (septic) conditions

Abstract: Changes in water quality in sewers may have significant effects on the performance of treatment plants. Experiments have been carried out in two pilot scale sewers for studies of biofilm growth and changes of water quality with anoxic (dosage of nitrate) and anaerobic (septic) conditions, respectively. The thickness of the biofilm in the anoxic sewer was 1-2 mm as compared to 0.3-0.6 mm in the septic sewer at a water velocity of 0.5 m/s. An increase in the water velocity from 0.002 m/s to 0.5 m/s gave thicker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…There was not a big difference between the nitrate removal with each nitrate dose (2.5 and 3.5 mg/L NO 3 ‐N). In this pipeline stretch, the consumption ratio between COD S and nitrate was in the range of 1.2 to 2.4 g COD S /g NO 3 ‐N in both series of experiments, which is far below the consumption ratio of 4.8 g COD S /g NO 3 ‐N between dissolved organic matter and nitrate when readily biodegradable organic matter is available ( Æs⊘y et al, 1997 ). However, it should be taken into account that the study by Æs⊘y et al (1997) was made in a sewer, with wastewater and biofilm characteristics quite different from the sewer under study.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…There was not a big difference between the nitrate removal with each nitrate dose (2.5 and 3.5 mg/L NO 3 ‐N). In this pipeline stretch, the consumption ratio between COD S and nitrate was in the range of 1.2 to 2.4 g COD S /g NO 3 ‐N in both series of experiments, which is far below the consumption ratio of 4.8 g COD S /g NO 3 ‐N between dissolved organic matter and nitrate when readily biodegradable organic matter is available ( Æs⊘y et al, 1997 ). However, it should be taken into account that the study by Æs⊘y et al (1997) was made in a sewer, with wastewater and biofilm characteristics quite different from the sewer under study.…”
Section: Resultsmentioning
confidence: 79%
“…In this pipeline stretch, the consumption ratio between COD S and nitrate was in the range of 1.2 to 2.4 g COD S /g NO 3 ‐N in both series of experiments, which is far below the consumption ratio of 4.8 g COD S /g NO 3 ‐N between dissolved organic matter and nitrate when readily biodegradable organic matter is available ( Æs⊘y et al, 1997 ). However, it should be taken into account that the study by Æs⊘y et al (1997) was made in a sewer, with wastewater and biofilm characteristics quite different from the sewer under study. Because the removal of COD S corresponded to only a part of the theoretical consumption of COD based on the nitrate removal, it may be concluded that the other part was taken from particulate compounds (the average total COD consumption was above 4.8 g COD/g NO 3 ‐N with both doses).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Biofilms in blackcolored anaerobic reactors with slightly rougher (grainy) visible texture are coating the surface of the bio ball medium. According to [17], characteristics of the biofilm that grows in anaerobic conditions seen black colored, more rugged and compact. Biofilm in aerobic reactor looks brownish color with the texture that looks more slippery and thicker coated the surface of bio ball media.…”
Section: Seeding Resultsmentioning
confidence: 99%